The species diversity of the genus Gallotia (Sauria: Lacertidae) during the Holocene on La Gomera (Canary Islands) and the Latin names of Gomeran giant lizards - Mateo, José A.; Crochet, Pierre-André; Afonso, Oscar M. (Zootaxa, 2011)
The importance of appropriate identification of a species prior to the adoption of an effective species conservation plan should not be underestimated. This precondition is not generally problematic. However, erroneous identification leads to unsuitable conservation measures (Daugherty et al. 1990) being drawn up. This may be the case of the “critically endangered” gomeran giant lizard (Cox et al. 2006).